2020
DOI: 10.3389/fcell.2020.00273
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Nervous System Development and Disease

Abstract: The rapid advance of RNA sequencing technologies contributed to a deep understanding of transcriptome composition and has allowed the discovery of a large number of non-coding RNAs (ncRNAs). The ability of these RNA molecules to be engaged in intricate and dynamic interactions with proteins and nucleic acids led to a great expansion of gene expression regulation mechanisms. By this matter, ncRNAs contribute to the increase in regulatory complexity that becomes highly specific between tissues and cell types. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 219 publications
0
35
0
Order By: Relevance
“…The most notable example is in cerebellum and maps in NEAT1 . NEAT1 is a ubiquitously expressed long non-coding RNA (lncRNA) involved in a plethora of neurospecific processes such as brain development and aging (An et al, 2018 ; Pereira Fernandes et al, 2018 ; Salvatori et al, 2020 ). Recent transcriptomic studies on human central nervous system revealed altered NEAT1 levels in AD (Spreafico et al, 2018 ), PD (Simchovitz et al, 2019 ), and in schizophrenia (Katsel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most notable example is in cerebellum and maps in NEAT1 . NEAT1 is a ubiquitously expressed long non-coding RNA (lncRNA) involved in a plethora of neurospecific processes such as brain development and aging (An et al, 2018 ; Pereira Fernandes et al, 2018 ; Salvatori et al, 2020 ). Recent transcriptomic studies on human central nervous system revealed altered NEAT1 levels in AD (Spreafico et al, 2018 ), PD (Simchovitz et al, 2019 ), and in schizophrenia (Katsel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most notable example is in cerebellum and maps in NEAT1. NEAT1 is a ubiquitously expressed long non-coding RNA (lncRNA) involved in a plethora of neurospecific processes such as brain development and aging (58-60). Recent transcriptomic studies on human CNS revealed altered NEAT1 levels in AD (61),PD (62) and in schizophrenia (63).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence emphasizes the importance of lncRNAs in CNS development and (dys)function. Genome-wide association studies and comparative transcriptomic analyses link lncRNA deregulation and dysfunction to multiple human diseases, including a wide range of neurodevelopmental, neuropsychiatric, and neurodegenerative conditions ( Salta and De Strooper, 2017 ; Salvatori et al, 2020 ). The identification of multiple natural antisense transcripts (NATs), a class of lncRNAs, at distinct human loci associated with hereditary neurodegenerative disorders including Alzheimer’s Disease, Frontotemporal Dementia, Parkinson’s Disease, Amyotrophic Lateral Sclerosis and Huntington’s Disease further illustrates the potential role of lncRNAs in the expression regulation of neurodegeneration-related genes ( Zucchelli et al, 2019 ).…”
Section: Mechanisms Of Lncrnas In Neurological Disordersmentioning
confidence: 99%